Battery negative electrode active material and method for producing the same, battery negative electrode, and secondary battery

JP2025505897AActive Publication Date: 2025-03-04BERZELIUS (NANJING) CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024530032
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-11-26
Filing Date
2022-11-16
Publication Date
2025-03-04
Estimated Expiration
2042-11-16

AI Technical Summary

Benefits of technology

【0024】 本願に係る電池用の負極活性材料は、使用時にエネルギー密度が高く、動力学的性能が良い電気化学的特性を有する。このような負極活性材料を用いて製造された電池は、高エネルギー密度や優れた倍率放電性能及び急速充電性能などの利点がある。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505897000001_ABST
    Figure 2025505897000001_ABST
Patent Text Reader

Abstract

The present invention provides a battery negative electrode active material and a manufacturing method thereof, a battery negative electrode, and a secondary battery. The battery negative electrode active material includes negative electrode active material particles containing a silicon oxide compound and lithium element, and the negative electrode active material particles have a first diffraction peak in the range of 2θ=18.78°±0.2° and a second diffraction peak in the range of 2θ=47.4°±0.3° in X-ray diffraction of Cu-Kα rays, the half width of the first diffraction peak is A>0.34°, the half width of the second diffraction peak is B, and B / A≧1.3. The battery negative electrode active material according to the present application has electrochemical properties with high energy density and good dynamic performance during use. A battery manufactured using such a negative electrode active material has advantages such as high energy density, excellent multiply discharge performance, and fast charge performance.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the field of batteries, and in particular to a battery negative electrode active material and a method for producing the same, a battery negative electrode, and a secondary battery. [Background technology]

[0002] In recent years, with the development of various portable electronic devices and electric vehicles, the demand for batteries with high energy density and long cycle life is increasing. Currently, the negative electrode active material of commercially available lithium-ion batteries is mainly graphite, but its low theoretical capacity (372 mAh / g) limits further improvement of the battery energy density. On the other hand, silicon negative electrode active materials have the characteristic of very high capacity (lithium intercalation state is Li at room temperature). 15 S 4 The theoretical lithium storage capacity is about 3600mAh / g), which is about 10 times the theoretical capacity of the graphite anode active material currently on the market. It has the advantage of high capacity that other anode active materials cannot match. Therefore, it has been the focus of research and development in academia and industry for many years, and is gradually moving from laboratory development to market commercialization.

[0003] At present, there are three main types of silicon anode active materials being developed. First, silicon alone (including nanosilicon, porous silicon, amorphous silicon, etc.) and composite materials with carbon materials; second, alloy materials combining silicon with other metals (e.g., iron, manganese, nickel, chromium, cadmium, tin, copper, etc.) and nonmetals (carbon, nitrogen, phosphorus, boron, etc.); and third, composite materials of silicon oxide compounds and carbon materials. Among the above three structures, silicon alone has the highest theoretical capacity and therefore the highest theoretical energy density. However, silicon alone anode active materials have a significant volume effect during lithium insertion / extraction, with a volume change rate of about 300%, which leads to powdering of the electrode material and separation of the electrode material from the current collector. In addition, silicon anode active materials continue to expand and contract during battery charging and discharging, and the resulting fresh interface is exposed to the electrolyte to form a new SEI film, which continuously consumes the electrolyte and reduces the cycle characteristics of the electrode material. The above drawbacks have severely limited the commercial application of silicon-based negative electrodes.

[0004] Since silicon oxide compounds have a relatively large amount of inactive materials, their capacity is lower than that of the negative electrode active material consisting of silicon alone; however, at the same time, due to the presence of these inactive components, the expansion of silicon during the cycling process is effectively suppressed by the inactive phase, so that its cycling stability has obvious advantages.

[0005] Silicon oxide compounds also have their own problems. When the material is first inserted with lithium, the surface of the particles tends to undergo many side reactions with the electrolyte, which tends to produce a relatively thick SEI film. In addition, substances that cannot reversibly release lithium, such as lithium silicate and lithium oxide, are produced inside the particles, which leads to irreversible loss of lithium ions in the battery. The above two irreversible reactions result in low initial coulombic efficiency of lithium-ion batteries containing silicon oxide compound anodes, which limits the improvement of the energy density of the whole battery. In addition, silicon oxide compounds have problems such as low ionic and electronic conductivity, and relatively low coulombic efficiency during the battery cycle process. In response to the above problems, scientific researchers have made the following improvements.

[0006] Specifically, the surface layer of the silicon oxide compound can be coated with a conductive material such as a carbon film in order to improve the conductivity of the silicon oxide compound and obtain a high capacity and a better cycle retention rate. In order to improve the initial charge and discharge efficiency, lithium element can be inserted into the silicon oxide compound, for example, by kneading the silicon oxide compound with lithium metal at high temperature, by using an electrochemical method to insert lithium element into the silicon oxide compound anode, or by using a high-energy mixer to mix the silicon oxide compound with metallic lithium or an organolithium compound as a lithiating agent and reacting them in situ, or by reacting a lithium-containing compound with the silicon oxide compound at high temperature to insert lithium element into the silicon oxide compound. At the same time, the microstructure and crystalline phase composition of the silicon oxide compound have a significant effect on its electrochemical performance, and in order to obtain better cycle characteristics, many studies have focused on reducing the size of silicon microcrystals inside the silicon oxide compound. However, how to improve the kinetic properties of the silicon oxide compound so that the secondary battery using this anode has better multiplier discharge and fast charge performance remains one of the difficult problems in the industry.

[0007] The contents of the background art are to the best of the applicant's knowledge and are not intended to represent the prior art in this technical field. Summary of the Invention [Problem to be solved by the invention]

[0008] The present invention provides a battery negative electrode active material that addresses the shortcomings of the prior art. [Means for solving the problem]

[0009] A battery negative electrode active material, comprising negative electrode active material particles including a silicon oxide compound and elemental lithium; the negative electrode active material particles have a first diffraction peak in the range of 2θ=18.78°±0.2° and a second diffraction peak in the range of 2θ=47.4°±0.3° in X-ray diffraction using Cu-Kα radiation; The half width of the first diffraction peak is A>0.34°, the half width of the second diffraction peak is B, and B / A≧1.3.

[0010] In some embodiments of the invention, 0.43°≦A≦3° and 1.5≦B / A≦20, preferably 0.55°≦A≦2° and 1.8≦B / A≦15.

[0011] In some embodiments of the present invention, the peak area of ​​the first diffraction peak is C, the sum of peak areas of all diffraction peaks in the range of 2θ=10° to 60° in X-ray diffraction of the negative electrode active material particles using Cu-Kα rays is D, and C / D≧0.03, preferably 0.05≦C / D≦0.2.

[0012] In some embodiments of the present invention, the negative electrode active material particles have a third diffraction peak in the range of 2θ=22° to 23° in Cu-Kα X-ray diffraction, the peak area of ​​the third diffraction peak is E, and E / D≦0.02.

[0013] In some embodiments of the present invention, the negative electrode active material particles have a fourth diffraction peak in the range of 2θ=23.4° to 25.2° in Cu-Kα X-ray diffraction, and F / C≦6, preferably F / C≦3, and more preferably F / C≦1, where F is the peak area of ​​the fourth diffraction peak.

[0014] In some embodiments of the present invention, the negative electrode active material particles further contain monomeric nanosilicon, and the median particle size of the monomeric nanosilicon dispersed within the negative electrode active material particles is 0.1 to 35 nm, preferably 0.5 to 20 nm, and more preferably 1 to 15 nm.

[0015] In some embodiments of the present invention, the silicon content in the negative electrode active material particles is 30 to 80 wt %, preferably 35 to 65 wt %, and more preferably 40 to 65 wt %.

[0016] In some embodiments of the present invention, the negative electrode active material particles further include a carbon film layer located on a surface thereof.

[0017] In some embodiments of the present invention, the carbon film layer has a thickness of 0.001 to 5 μm, preferably 0.005 to 2 μm, and more preferably 0.01 to 1 μm.

[0018] In some embodiments of the present invention, the mass proportion of the carbon film layer is 0.01 to 20 wt %, preferably 0.1 to 15 wt %, and more preferably 1 to 12 wt %, of the total mass of the negative electrode active material particles.

[0019] The present invention also provides a method for producing a battery negative electrode active material, comprising producing negative electrode active material particles, The negative electrode active material particles are produced by Providing silicon oxide compound particles; Inserting lithium element into the silicon oxide compound particles, the negative electrode active material particles have a first diffraction peak in the range of 2θ=18.78°±0.2° and a second diffraction peak in the range of 2θ=47.4°±0.3° in X-ray diffraction using Cu-Kα radiation; The half width of the first diffraction peak is A>0.34°, the half width of the second diffraction peak is B, and B / A≧1.3.

[0020] In some embodiments of the present invention, preparing the negative electrode active material particles further comprises coating a part or all of the surfaces of the silicon oxide compound particles with carbon.

[0021] In some embodiments of the present invention, the lithium element is inserted into the silicon oxide compound particles after a part or all of the surface of the silicon oxide compound particles is coated with carbon.

[0022] The present invention also provides a battery negative electrode, a battery negative electrode active material as described above, or The battery negative electrode active material is produced by the method as described above.

[0023] The present invention also provides a secondary battery including the above-mentioned battery negative electrode. Effect of the Invention

[0024] The negative electrode active material for a battery according to the present invention has electrochemical properties that provide high energy density and good dynamic performance during use. A battery manufactured using such a negative electrode active material has advantages such as high energy density, excellent multiple discharge performance, and fast charge performance. [Brief description of the drawings]

[0025] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. [Figure 1] 1 is a process flow chart for manufacturing a negative electrode active material according to an exemplary embodiment of the present application. [Diagram 2] 4 is a process flow chart for manufacturing a negative electrode active material according to another exemplary embodiment of the present application. [Diagram 3] FIG. 1 is a schematic diagram of half-width by XRD pattern fitting. [Figure 4] 1 is an XRD pattern of a negative electrode active material produced according to an exemplary embodiment of the present application. [Diagram 5] 1 is a SEM photograph of a negative electrode active material produced according to an exemplary embodiment of the present application, magnified at 10,000 times; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, the specific embodiments of the present invention will be described in more detail in combination with drawings and embodiments, so that the aspects of the present invention and the advantages of its various aspects can be better understood. However, the specific embodiments and examples described below are for illustrative purposes only and do not limit the present invention.

[0027] In particular, it goes without saying that all similar replacements and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The method and use of the present invention have been described by the preferred embodiments, and it is obvious that the method and use described herein can be modified or appropriately modified and combined to realize and apply the technology of the present invention without departing from the content, spirit and scope of the present invention.

[0028] [Negative electrode active material] The present invention provides a negative electrode active material for a battery, the negative electrode active material particles including a silicon oxide compound and a lithium element. In the present invention, the silicon oxide compound is preferably in the form of particles.

[0029] The negative electrode active material particles of the present invention have a first diffraction peak in the range of 2θ=18.78°±0.2° in X-ray diffraction of Cu-Kα rays, and the diffraction peak corresponds to Li 2 SiO 3 In the present invention, the half width of the first diffraction peak is A>0.34°.

[0030] Furthermore, the negative electrode active material particles of the present invention have a second diffraction peak in the range of 2θ=47.4°±0.3° in X-ray diffraction using Cu-Kα radiation. This diffraction peak is a diffraction peak of the Si(220) crystal plane. In the present invention, the half-width of the second diffraction peak is B, and B / A≧1.3.

[0031] Furthermore, the value of A may satisfy 0.43°≦A≦3°, and 0.55°≦A≦2°.

[0032] Furthermore, the B / A value may satisfy 1.5≦B / A≦20. Furthermore, the B / A value may satisfy 1.8≦B / A≦15.

[0033] The present invention relates to Li 2 SiO 3The half-width of the diffraction peak of the Si(220) crystal plane and the Li phase is selected within the above range in order to obtain a negative electrode active material having an appropriate crystal grain size, a relatively uniform crystal domain structure within the grain, and good processability. 2 SiO 3 The larger the half-width of the diffraction peaks of the Li and Si phases (i.e., the larger the A and B values), the more likely it is that the Li phase is 2 SiO 3 The Li phase and the Si phase are closer to an amorphous structure, the crystal grains are smaller, the hindrance of the solid-phase migration of lithium ions inside the particles is smaller, and the dynamic performance is improved. However, the amorphous Li 2 SiO 3 The phase has poor stability and is prone to side reactions with water and air, forming strongly alkaline lithium-containing compounds, which will have a certain negative impact on the electrochemical performance of the material. Therefore, the A value defined by the present invention is preferably in the range of 0.43°≦A≦3°, more preferably in the range of 0.55°≦A≦2°.

[0034] On the other hand, Li 2 SiO 3 The Li phase and the Si phase are mutually dispersed, 2 SiO 3 When the grain size ratio of the Si phase to the Si phase is within a suitable range, the particles can have a suitable grain size, while ensuring that the internal microscale crystal domain structure is relatively uniform. When the Si phase inside the particles undergoes repeated lithium desorption and insertion and expansion and contraction, the structure of the present invention is favorable for uniform release of microscale stress inside the particles, reducing the particle rupture caused by stress unevenness, thereby reducing irreversible capacity loss. The present invention controls the A value and B / A value within the above range, and is favorable for obtaining a negative electrode active material with good dynamic performance, uniform internal crystal domain structure, and high reversible capacity.

[0035] In some embodiments of the present invention, the peak area of ​​the first diffraction peak is C, the sum of the peak areas of all the diffraction peaks of the negative electrode active material particles in the range of 2θ=10° to 60° is D (the peak area is obtained by removing the linear background area between 2θ=10° to 60°), and the ratio of C / D is ≧0.03. Furthermore, the C / D value can satisfy 0.05≦C / D≦0.2.

[0036] In some embodiments of the present invention, the negative electrode active material particles of the present invention have a third diffraction peak in the range of 2θ=22° to 23° in X-ray diffraction using Cu-Kα radiation. 4 SiO 4 The peak area of ​​the third diffraction peak is E, and E / D is ≦0.02.

[0037] Furthermore, the negative electrode active material particles of the present invention have a fourth diffraction peak in the range of 2θ=23.4° to 25.2° in X-ray diffraction using Cu-Kα radiation. 2 S 2 O 5 The Li 2 S 2 O 5 The peak area of ​​the diffraction peak is F, and F / C≦6.

[0038] Furthermore, the F / C value may satisfy F / C≦3. Furthermore, the F / C value may satisfy F / C≦1.

[0039] The present invention relates to a method for producing a negative electrode active material particle having a Li 2 SiO 3 , Li 4 SiO 4 , and Li 2 S 2 O 5 It is preferable to limit the proportion of the Li phase to some extent. 2 SiO 3 and Li 2 S 2 O 5 is preferably the main phase, and Li 4 SiO 4Avoid too high a proportion of the Li phase. 4 SiO 4 A relatively high proportion of the Li phase is likely to promote the enhancement of the crystallinity of Si and to lead to the inhomogeneity of the microscale crystal domain structure inside the grains. 2 SiO 3 , Li 4 SiO 4 , and Li 2 S 2 O 5 Controlling the ratio of the phases within the above range is advantageous in obtaining a negative electrode active material having a high reversible capacity, a uniform internal crystal domain structure, and good dynamic performance.

[0040] In some embodiments of the present invention, the median particle size of the silicon oxide compound particles is 0.2 to 20 microns, preferably 1 to 15 microns, and more preferably 3 to 13 microns.

[0041] In some embodiments of the present invention, the silicon oxide compound particles further contain monomeric nanosilicon. The monomeric nanosilicon can be uniformly dispersed in the negative electrode active material particles. The monomeric nanosilicon can be present in the silicon oxide compound particles in the form of nanoparticles, and the median particle size is 0.1 to 35 nm, preferably 0.5 to 20 nm, and more preferably 1 to 15 nm. The particles within this particle size range have a relatively small particle expansion and are not easily ruptured after undergoing a cycle of lithium ion insertion and desorption, so that the cycle expansion of the lithium ion secondary battery using the material is small and the cycle is stable.

[0042] In some embodiments of the present invention, the silicon content in the negative electrode active material particles is 30 to 80 wt%, preferably 35 to 65 wt%, and more preferably 40 to 65 wt%, so that the material has a high reversible capacity.

[0043] In some embodiments of the present invention, the surface of the negative electrode active material particles is coated with a carbon film layer. The carbon film layer covers a part or the whole of the surface of the silicon oxide compound. The thickness of the carbon film layer is 0.001 to 5 μm, preferably 0.005 to 2 μm, and more preferably 0.01 to 1 μm. The presence of the carbon film layer effectively improves the electrical conductivity of the particles and reduces the contact resistance between the particles in the negative electrode piece and between the negative electrode piece and the current collector, thereby improving the efficiency of lithium desorption / insertion of the material, reducing the polarization of the lithium ion battery, and promoting its cycle stability.

[0044] In some embodiments of the present invention, the mass proportion of the carbon film layer is 0.01 to 20 wt %, preferably 0.1 to 15 wt %, and more preferably 1 to 12 wt %, of the total mass of the negative electrode active material particles.

[0045] The negative electrode active material of the battery according to the present invention has electrochemical properties such as high energy density and good dynamic performance during use, and a battery manufactured using such a negative electrode active material has advantages such as high energy density, excellent multiple discharge performance, and rapid charge performance.

[0046] [Method of manufacturing negative electrode active material] FIG. 1 is a process flow diagram of the above-mentioned negative electrode active material according to an exemplary embodiment of the present application.

[0047] According to some embodiments, in step S301, silicon oxide compound particles are prepared. The specific manufacturing process can be performed by the following steps. First, a mixture of metal silicon powder and silica powder is heated in a temperature range of 900°C to 1600°C under an inert gas atmosphere or under reduced pressure conditions to generate silicon oxide gas, and the molar ratio of metal silicon powder to silica powder can be set in the range of 0.5 to 1.5. The gas generated by the raw material heating reaction is deposited on an adsorption plate. When the temperature in the reactor is lowered to 100°C or less, the deposit is removed and crushed and powdered using equipment such as a ball mill or a jet mill to obtain silicon oxide compound particles.

[0048] Next, the process proceeds to step S303, where lithium elements are inserted into the silicon oxide compound particles.

[0049] The present invention can utilize the following lithium element insertion method (lithium doping modification method).

[0050] 1) Electrochemical method The electrochemical bath includes four components: a bath, an anode electrode, a cathode electrode, and a power source, and the anode electrode and the cathode electrode are respectively connected to both ends of the power source. At the same time, the anode electrode is connected to a lithium source, and the cathode electrode is connected to a container containing silicon oxide compound particles. The bath is filled with an organic solvent, and the lithium source (anode electrode) and the container containing silicon oxide compound particles (cathode electrode) are immersed in the organic solvent. After the power is turned on, the lithium ions are inserted into the silicon oxide compound structure due to the occurrence of an electrochemical reaction, and lithium-doped modified silicon oxide compound particles are obtained. The above organic solvent can be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, dimethyl sulfoxide, and other solvents. In addition, the organic solvent also contains an electrolyte lithium salt, and lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 The lithium source (anode electrode) may be a lithium foil or a lithium compound such as lithium carbonate, lithium oxide, lithium hydroxide, lithium cobalt oxide, lithium iron phosphate, lithium manganate, lithium vanadium phosphate, or lithium nickel oxide.

[0051] 2) Liquid phase doping method Metallic lithium, an electron transfer catalyst, and silicon oxide compound particles are added to an ether-based solvent, and the solution is heated while stirring in a non-oxidizing atmosphere until the metallic lithium in the solution is completely disappeared to maintain a constant temperature reaction. Due to the action of the electron transfer catalyst, metallic lithium can be dissolved in the ether-based solvent and form a lithium ion coordination compound, which has a lower reduction potential, and reacts with the silicon oxide compound, and the lithium ion can enter the silicon oxide compound structure. The electron transfer catalyst includes biphenyl, naphthalene, etc. The ether-based solvent includes methyl butyl ether, ethylene glycol monobutyl ether, tetrahydrofuran, dimethoxyethane, etc. The constant temperature reaction temperature is 25 to 200°C. The non-oxidizing atmosphere is provided by at least one gas of nitrogen, argon, hydrogen, or helium.

[0052] 3) Thermal doping method Silicon oxide compound particles are uniformly mixed with a lithium-containing compound, and then heat-treated in a non-oxidizing atmosphere. The lithium-containing compound includes lithium hydroxide, lithium carbonate, lithium oxide, lithium peroxide, lithium hydride, lithium nitrate, lithium acetate, lithium valerate, and the like. The mixing method uses any one of a high-speed disperser, a high-speed stirrer, a ball mill, a taper mixer, a spiral mixer, a stirring mixer, and a VC mixer. The heat treatment equipment is any one of a rotary furnace, a ladle refining furnace, an inner pot furnace, a roller kiln, a pusher kiln, an atmospheric box furnace, and a tube furnace. The temperature of the heat treatment is 400°C to 850°C, preferably 550°C to 800°C, and more preferably 550°C to 750°C, the warming time is 1 to 12 hours, preferably 2 to 12 hours, and more preferably 4 to 12 hours, and the temperature rise rate is greater than 0.1°C / min and less than 10°C / min, preferably 0.1 to 5°C / min, and more preferably 0.1 to 3°C / min. The non-oxidizing atmosphere is provided by at least one gas selected from the group consisting of nitrogen, argon, hydrogen, and helium.

[0053] The inventors of the present application have found through research that in the above-mentioned heat treatment lithium doping reaction process, the selection of the heat treatment temperature, the warming time and the heating rate have a significant impact on the crystal structure of the obtained negative electrode active material and the uniformity of the micro-scale crystal domains inside the particles, thereby affecting the dynamic performance and cycle stability of the material. The higher the heat treatment temperature, the stronger the crystallinity of the obtained negative electrode active material becomes, and the more the Si phase and lithium silicate phase (Li X SiO Y ) is obtained, which deteriorates the dynamic performance of the material. On the other hand, the selection of the warming time and the warming rate greatly affect the uniformity of the crystal domain inside the material. If the warming rate is too fast, it is easy to cause the particles to be heated non-uniformly, resulting in excessive growth of local crystal grains. On the other hand, if the warming time is too short, it is easy to cause non-uniform lithium doping inside the particles, resulting in lithium-rich outer shells and lithium-poor cores in the particles, which also results in local crystal grain growth. Therefore, the above heat treatment temperature, warming time and warming rate range are preferred, which are advantageous for obtaining a negative electrode active material with a uniform internal crystal domain structure, appropriate crystal grain size, good dynamic performance and high reversible capacity.

[0054] In some embodiments of the present invention, the stoichiometric ratio of silicon to oxygen in the silicon oxide compound particles is 1:0.4-1:2, optionally 1:0.6-1:1.5, and further optionally 1:0.8-1:1.2, and includes trace amounts of other impurity elements in addition to silicon and oxygen.

[0055] According to some embodiments, as shown in FIG. 2, step S303 may further include a step S302 of coating the surface of the silicon oxide compound particles with a carbon film layer before inserting the lithium element.

[0056] The lithium element insertion step S303 is performed after the carbon film layer is coated, which can inhibit the growth of silicon crystal grains in the silicon oxide compound during heat treatment. This allows the nano-scale silicon single particles to be uniformly dispersed and fixed in the lithium silicate compound or silicone compound matrix, effectively inhibiting the expansion of silicon nanoparticles and preventing the silicon particles from gradually melting into larger particles during charging and discharging, thereby reducing the expansion deformation during battery cycling, reducing the electrical failure of the silicon material, and reducing the cycling expansion of the lithium ion secondary battery using the material, making the cycle stable. In addition, the carbon film layer coating step is performed before the lithium element is inserted, which is advantageous for coating a better quality and more complete carbon film layer.

[0057] In some embodiments of the present invention, the silicon oxide compound used may be a non-dispersed silicon oxide compound, or may be a silicon oxide compound that has been heat-treated for dispersing. The temperature for the heat treatment for dispersing may be 600°C to 1100°C, preferably 700°C to 1000°C, and more preferably 800°C to 1000°C.

[0058] The carbon film layer is directly obtained by chemical vapor deposition (CVD), and the carbon source used in CVD is a hydrocarbon compound gas. The decomposition temperature of the hydrocarbon compound gas is 600°C to 1100°C, preferably 700°C to 1000°C, and more preferably 800°C to 1000°C.

[0059] The carbon film layer may be obtained by first performing coating by carbon reaction and then performing carbonization by heat treatment in a non-oxidizing atmosphere. The carbon reaction coating method may use any one of a mechanical fusion machine, a VC mixer, a coating kettle, a spray dryer, a sand grinder, or a high-speed disperser, and the solvent used during coating may be one or a combination of water, methanol, ethanol, isopropyl alcohol, N-butanol, ethylene glycol, ether, acetone, N-methylpyrrolidone, methylbutanone, tetrahydrofuran, benzene, toluene, dimethylbenzene, N,N-dimethylformamide, N,N-dimethylacetamide, and chloroform. The carbon reaction source may be one or a combination of coal tar pitch, petroleum pitch, polyvinyl alcohol, epoxy resin, polyacrylonitrile, polymethylmethacrylate, glucose, sucrose, polyacrylic acid, and polyvinylpyrrolidone. The equipment used for the heat treatment carbonization may be any one of a rotary furnace, a ladle refining furnace, a roller kiln, a pusher kiln, an atmosphere box furnace, and a tube furnace. The temperature of the heat treatment carbonization is 600° C. to 1100° C., preferably 700° C. to 1000° C., and more preferably 800° C. to 1000° C., and the heat retention time is 0.5 to 24 hours. The non-oxidizing atmosphere may be provided by at least one gas selected from nitrogen, argon, hydrogen, and helium.

[0060] According to some embodiments, the silicon oxide compound particles may be completely, partially, or not at all coated with a carbon film layer.

[0061] [Method for characterizing negative electrode active materials] 1. Material testing: The negative active materials prepared according to each embodiment and comparative example are characterized using the following equipment. A Dandong Baite BetterSize 2000 type laser granulometer is used to measure the particle size distribution of the negative active material. A Rigaku miniflex 600 type powder X-ray diffractometer (XRD) is used to measure the components and crystal structure of the obtained negative material, with the 2θ angle range of 10° to 60°, the scanning speed of 1° / min, the step size of 0.02°, and the X-ray source power of 600w. In addition, as shown in FIG. 3, the method of measuring the half-width according to the present application is to remove the linear background between 10° and 60° from the X-ray diffraction spectrum measured using Jade software, and then perform fitting on the corresponding diffraction peak, and basically overlap the fitting peak with the measured spectrum, and read out the half-width of the fitting peak as the half-width of the corresponding diffraction peak. At the same time, the peak area of ​​the diffraction peak according to the present application is also measured as described above, using the peak area of ​​the fitting peak as the peak area of ​​the diffraction peak. A Hitachi SU8010 scanning electron microscope is used to observe the surface morphology of the negative electrode active material.

[0062] 2. Preparation of homogenate and electrode piece: Take 14 parts of the above negative electrode active material, 81 parts of artificial graphite, 2.5 parts of conductive additive, and 2.5 parts of adhesive, and apply homogenate under aqueous system, then dry and roll to obtain negative electrode piece containing the negative electrode active material of the present invention.

[0063] 3. Whole battery evaluation: The negative electrode pieces of the negative active materials prepared according to each embodiment and comparative example are cut, vacuum baked, wound together with paired positive electrode pieces and partition membrane, put into corresponding size aluminum shell, inject a certain amount of electrolyte, remove gas, seal, and obtain about 3.2Ah lithium ion whole battery after formation. The capacity, energy, and constant current charge ratio of the whole battery at 0.2C and 3C are measured using a battery tester from Shenzhen Newwill Electronics Co., Ltd.

[0064] The present invention will now be further described with reference to specific examples.

[0065] Example 1-1 1000 grams of silicon oxide compound particles having a median diameter of 5 microns and an atomic ratio of silicon to oxygen of 1:1 were prepared.

[0066] The silicon oxide compound powder, metallic lithium ribbon and biphenyl were placed in a sealable glass container, and methyl butyl ether was added and reacted under an argon atmosphere with stirring. After the reaction was completed and dried, the resulting powder was placed in an argon atmosphere and heat-treated to 850°C at a heating rate of 5°C / min, and then kept at that temperature for 2 hours, after which it was naturally cooled to obtain a lithium-doped silicon oxide compound powder. The XRD spectrum and SEM photograph of the material are shown in Figures 4 and 5.

[0067] The spectrum obtained by X-ray diffraction of Cu-Kα radiation is in the range of 2θ=18.78°±0.2°. 2 SiO 3 The material has a diffraction peak of the Si(220) crystal plane in the range of 2θ=47.4°±0.3°, the half-width of the diffraction peak is B, and B / A=4. The material has a diffraction peak of the Li(220) crystal plane in the range of 2θ=23.4° to 25.2°, the half-width of the diffraction peak is B, and the peak area of ​​the Li(220) crystal plane is C. 2 S 2 O 5 The diffraction peak of Li 2 S 2 O 5 The peak area of ​​the diffraction peak of Li in the range of 2θ=22° to 23° is defined as F. The sum of the peak areas of all the diffraction peaks in the range of 2θ=10° to 60° in the diffraction spectrum is defined as D (the peak area is obtained by removing the linear background area between 2θ=10° to 60°). The results are C / D=0.12 and F / C=0.4 (shown in Table 1). 4 SiO 4 Since it does not include the diffraction peak of the Li phase, 4 SiO 4 The diffraction peak area E of the phase can be considered as zero.

[0068] 14 parts of the above negative electrode active material, 81 parts of artificial graphite, 2.5 parts of conductive additive, and 2.5 parts of adhesive were taken and homogenized in an aqueous system. Some of the aqueous homogenized slurry was taken for water resistance and stability tests, and the other slurry was applied, followed by drying and rolling to obtain silicon-containing negative electrode pieces.

[0069] In this example, the results of the whole battery evaluation of the negative electrode active material were that the constant current charge ratio (CCCCR) was 75.9% at a 3C fast charge rate, the mass energy density was 261.5Wh / kg at a 3C discharge rate, and the ratio of the energy density at a 3C discharge rate to the energy density at a 0.2C discharge rate was 86.3%.

[0070] Example 1-2 1000 grams of silicon oxide compound particles with a median diameter of 5 microns were taken and placed in a CVD furnace. A coating reaction was carried out at 950°C using acetylene as the carbon source, resulting in silicon oxide compound particles completely coated with a carbon film layer, with the carbon film layer being 20 nm thick.

[0071] Next, lithium metal doping was performed using a thermal doping method. Specifically, the above particles were taken and mixed with a lithium-containing compound (e.g., lithium oxide, lithium hydride, lithium hydroxide, lithium carbonate, etc.), and the mixed powder was heat-treated in an argon atmosphere to increase the temperature up to 800°C at a heating rate of 3°C / min, and then kept at that temperature for 3 hours. After natural cooling, a lithium-containing silicon oxide compound coated with a carbon film was obtained.

[0072] As shown in Table 1 below, in this example, A=0.43, B / A=4, C / D=0.12, and F / C=0.4. The material is Li 4 SiO 4 It does not include the diffraction peaks of the phase.

[0073] In this example, the results of the whole battery evaluation of the negative electrode active material were that the constant current charge ratio (CCCCR) was 79.84% at a 3C fast charge rate, the mass energy density was 268.9Wh / kg at a 3C discharge rate, and the ratio of the energy density at a 3C discharge rate to the energy density at a 0.2C discharge rate was 89.4%.

[0074] Examples 1-3 to 1-16 The particle size of the silicon oxide compound was controlled to 5 microns, and a carbon film layer with a thickness of 20 nm was coated on the surface of the silicon oxide compound using the aforementioned chemical vapor deposition or carbon reactive coating method. The lithium doping reaction was then carried out using the aforementioned electrochemical doping method, thermal doping method, or liquid phase doping method. By adjusting parameters such as the carbonization temperature in the carbon film coating process, the lithium doping amount in the lithium doping reaction process, the heat treatment temperature, the warming time, and the heating rate, the crystal structure of the material and the uniformity of the microscale crystal domains were changed to obtain negative electrode active materials with different A values ​​and B / A values.

[0075] The results are shown in Table 1 below. Examples 1-3 to 1-16 are all Li 4 SiO 4 The diffraction peaks of the phases are not included. The 3C fast charge performance and 3C multiple discharge performance of these example materials are shown in Table 1.

[0076] Comparative Example 1-1 1000 grams of silicon oxide compound particles with a median diameter of 5 microns and a silicon to oxygen atomic ratio of 1:1 were prepared and subjected to a lithium doping reaction using a liquid phase doping method. The obtained powder was heat-treated in an argon atmosphere, heated to 900°C at a heating rate of 15°C / min, and then kept at that temperature for 2 hours, after which it was naturally cooled to obtain lithium-doped silicon oxide compound powder.

[0077] Comparative Example 1-2 1000 grams of silicon oxide compound particles with a median diameter of 5 microns were taken and placed in a CVD furnace. A coating reaction was carried out at 1200°C using acetylene as the carbon source. Lithium metal doping was then carried out using an electrochemical method to obtain a lithium-containing silicon oxide compound coated with a carbon film.

[0078] Table 1 shows the material structure parameters (A value, B / A value, etc.) of Comparative Examples 1-1 and 1-2, as well as the 3C rapid charging performance and 3C multiplied discharge performance.

[0079] [Table 1]

[0080] As can be seen by comparing with the data of Examples 1-1 to 1-16, the energy density, rapid charge performance, and multiply discharge performance of Comparative Example 1-1 were poor. This was because its A value was 0.25, and the crystal grain size was large, which affected the kinetics of the material. Meanwhile, the energy density, rapid charge performance, and multiply discharge performance of Comparative Example 1-2 were also poor, but although its A value was greater than 0.34, its B / A value was only 1, and the kinetics of the material was also similarly affected.

[0081] As can be seen from a comparison of the results of Examples 1-1 to 1-16, when the A value satisfies 0.55°≦A≦2° and the B / A value satisfies 1.8≦B / A≦15, the Li 2 SiO 3 The grains of the Li and Si phases are small, and at the same time, 2 SiO 3 The Li phase has a certain degree of crystallinity to maintain the stability of the material, and the structure of the microscale crystal domains inside the material particles is more uniform, 2 SiO 3 The grain sizes of the Si phase and the Si phase are not significantly different. Therefore, the material has little hindrance to the solid-phase migration of lithium ions inside the particles, and has good dynamic performance. Moreover, this structure is favorable for uniform release of micro-scale stress inside the particles, reducing particle rupture caused by uneven stress and reducing irreversible capacity loss. Therefore, the embodiment of this section has optimal 3C fast charging performance and 3C multiply discharging performance while having higher energy density.

[0082] Examples 2-1 to 2-6 The particle size of the silicon oxide compound was controlled to 5 microns, and a carbon film layer with a thickness of 20 nm was coated on the surface of the silicon oxide compound using the above-mentioned chemical vapor deposition or carbon reactive coating method. Then, the lithium doping reaction was carried out using the above-mentioned electrochemical doping method, thermal doping method, or liquid phase doping method. By adjusting the parameters such as the lithium doping amount, heat treatment temperature, warming time, and heating rate during the lithium doping reaction, negative electrode active material materials with different C / D values ​​were obtained. The details are shown in Table 2.

[0083] [Table 2]

[0084] As can be seen from a comparison of the data of Examples 2-1 to 2-6, when the C / D value is too small (Example 2-6), the energy density of the battery using the material is affected to some extent, and when the C / D value is between 0.05 and 0.2, the 3C rapid charge performance, 3C multiple discharge performance, and energy density are good.

[0085] Examples 3-1 to 3-4 The particle size of the silicon oxide compound was controlled to 5 microns, and a carbon film layer with a thickness of 20 nm was coated on the surface of the silicon oxide compound using the above-mentioned chemical vapor deposition or carbon reactive coating method. Then, the lithium doping reaction was carried out using the above-mentioned electrochemical doping method, thermal doping method, or liquid phase doping method. By adjusting the parameters such as the lithium doping amount, heat treatment temperature, warming time, and heating rate during the lithium doping reaction, negative electrode active materials with different E / D values ​​were obtained. The details are shown in Table 3.

[0086] [Table 3]

[0087] As can be seen from a comparison of the data in Examples 3-1 to 3-4, when E / D is greater than 0.02, the energy density, fast charging performance, and rapid discharge performance of the battery using the material are affected to a certain extent. This is because Li 4SiO 4 This is because when the proportion of this phase is relatively large, the crystallinity of Si is likely to be enhanced and the microscale crystal domain structure inside the particle is likely to become non-uniform.

[0088] Examples 4-1 to 4-5 As in Examples 3-1 to 3-4, negative electrode active materials having different F / C values ​​were obtained by adjusting parameters such as the amount of lithium doped during the lithium doping reaction, the heat treatment temperature, the warming time, and the heating rate. The specific values ​​are shown in Table 4.

[0089] [Table 4]

[0090] As can be seen from a comparison of the data of Examples 4-1 to 4-5, when F / C is greater than 6, the energy density, rapid charge performance, and multiply discharge performance of the battery using the material are affected to some extent.

[0091] It is clear that the above examples are only for clarifying the examples described herein, and do not limit the embodiments. Those skilled in the art can make other different types of changes and variations based on the above description. It is not necessary and cannot be exhaustively described here. Any obvious changes or variations caused thereby are still within the protection scope of the present invention.

Claims

1. A battery negative electrode active material, comprising negative electrode active material particles including a silicon oxide compound and elemental lithium; the negative electrode active material particles have a first diffraction peak in the range of 2θ=18.78°±0.2° and a second diffraction peak in the range of 2θ=47.4°±0.3° in X-ray diffraction using Cu-Kα radiation; A battery negative electrode active material, characterized in that the half width of the first diffraction peak is A>0.34°, the half width of the second diffraction peak is B, and B / A≧1.

3.

2. 2. The battery negative electrode active material according to claim 1, characterized in that 0.43°≦A≦3° and 1.5≦B / A≦20, preferably 0.55°≦A≦2° and 1.8≦B / A≦15.

3. The battery negative electrode active material according to claim 1, characterized in that C is a peak area of ​​the first diffraction peak, D is a sum of peak areas of all diffraction peaks in the range of 2θ=10° to 60° in X-ray diffraction of the negative electrode active material particles using Cu-Kα rays, and C / D≧0.03, preferably 0.05≦C / D≦0.

2.

4. The negative electrode active material particles have a third diffraction peak in the range of 2θ=22° to 23° in X-ray diffraction with Cu-Kα rays, a peak area of ​​the third diffraction peak is E, a sum of peak areas of all diffraction peaks in the range of 2θ=10° to 60° in X-ray diffraction with Cu-Kα rays of the negative electrode active material particles is D, and E / D≦0.

02.

5. The battery negative electrode active material according to claim 1, characterized in that a peak area of ​​the first diffraction peak is C, the negative electrode active material particles have a fourth diffraction peak in the range of 2θ=23.4° to 25.2° in Cu-Kα X-rays, and a peak area of ​​the fourth diffraction peak is F, where F / C≦6, preferably F / C≦3, and more preferably F / C≦1.

6. The negative electrode active material particles further comprise monomeric nanosilicon, and the median particle size of the monomeric nanosilicon dispersed in the negative electrode active material particles is between 0.1 and 35 nm, preferably between 0.5 and 20 nm, and more preferably between 1 and 15 nm.

7. 2. The battery negative electrode active material according to claim 1, wherein the silicon content in the negative electrode active material particles is 30 to 80 wt %, preferably 35 to 65 wt %, and more preferably 40 to 65 wt %.

8. The battery negative electrode active material of claim 1 , wherein the negative electrode active material particles further comprise a carbon film layer located on a surface thereof.

9. 9. The battery negative electrode active material according to claim 8, wherein the carbon membrane layer has a thickness of 0.001 to 5 μm, preferably 0.005 to 2 μm, and more preferably 0.01 to 1 μm.

10. The mass ratio of the carbon membrane layer is 0.01 to 20 wt %, preferably 0.1 to 15 wt %, more preferably 1 to 12 wt % of the total mass of the negative electrode active material particles.

11. 1. A method for producing a battery anode active material, comprising: The preparation of the negative electrode active material particles includes Providing silicon oxide compound particles; Inserting lithium element into the silicon oxide compound particles, the negative electrode active material particles have a first diffraction peak in the range of 2θ=18.78°±0.2° and a second diffraction peak in the range of 2θ=47.4°±0.3° in Cu-Kα X-rays; A method for producing a battery negative electrode active material, wherein the half width of the first diffraction peak is A>0.34°, the half width of the second diffraction peak is B, and B / A≧1.

3.

12. The method according to claim 11, wherein preparing the negative electrode active material particles further comprises coating a part or all of the surface of the silicon oxide compound particles with carbon.

13. The method according to claim 12, characterized in that the lithium element is inserted into the silicon oxide compound particles after a part or all of the surface of the silicon oxide compound particles is covered with carbon.

14. A battery negative electrode, A battery negative electrode active material according to any one of claims 1 to 10, or A battery negative electrode comprising a battery negative electrode active material produced by the method according to any one of claims 11 to 13.

15. A secondary battery comprising the battery negative electrode according to claim 14.

Citation Information

Patent Citations

  • Nonaqueous electrolyte battery and negative active material

    JP2007059213A

  • Negative electrode active material for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and manufacturing method of negative electrode material for nonaqueous electrolyte secondary battery

    JP2020113495A

  • Negative electrode active material, mixed negative electrode active material, aqueous negative electrode slurry composition, and method for producing negative electrode active material

    WO2020095558A1